Alienation: a key category for the analysis of oppression - Gomes da Costa, Renata; Soares Vieira, Monique (Argumentum, 2020)
This paper aims to analyse the roots of oppression. It hypothesises that alienation is the analytical key to understanding the various manifestations of oppression in bourgeois society. The course of the debate undertaken in this paper comes from Marx’s labour theories of value and exploitation, since we understand that they are structuring elements of social relations in capitalism.